2009
DOI: 10.1515/jpem.2009.22.3.195
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Surrogate Vascular Markers in Youth at Risk for Premature Cardiovascular Disease

Abstract: Premature cardiovascular disease (CVD) begins in youth--a crucial period when modification of the disease may have the greatest impact. Failure to diagnose preclinical CVD at this stage misses a major opportunity to prevent the long-term consequences of this disease. An array of surrogate vascular markers (SVMs) are now available that can determine the extent of preclinical vascular injury in the pediatric population. These SVMs include flow-mediated vasodilatation, carotid intima media thickness, arterial sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 98 publications
0
13
0
1
Order By: Relevance
“…Early diagnosis of preclinical atherosclerosis can be made by measurement of carotid artery intima-media thickness (cIMT), flow-mediated vasodilatation and arterial stiffness 4 . Carotid artery intima-media thickness is a reliable surrogate marker of atherosclerosis 5,6 .…”
mentioning
confidence: 99%
“…Early diagnosis of preclinical atherosclerosis can be made by measurement of carotid artery intima-media thickness (cIMT), flow-mediated vasodilatation and arterial stiffness 4 . Carotid artery intima-media thickness is a reliable surrogate marker of atherosclerosis 5,6 .…”
mentioning
confidence: 99%
“…Pediatric studies on environmental factors that may influence risk of CVD have investigated a range of CVD biomarkers (10). A range of CVD risk factors and vascular health biomarkers that have been measured in childhood are summarized in the Table 1.…”
Section: Early-life Origins Of Cvdmentioning
confidence: 99%
“…Various measures of vascular health, including carotid intimamedia thickness, pulse wave velocity, flow-mediated vasodilatation, high-sensitivity C-reactive protein, and cell adhesion molecules, have been suggested as valuable biomarkers of vascular health in pediatric epidemiological studies (10,24). Current data have demonstrated that in pediatric populations, adverse changes in these biomarkers are associated with a range of CVD risk factors, including elevated blood pressure, type 1 and 2 diabetes, obesity, and hypercholesterolemia.…”
Section: Measures Of Vascular Healthmentioning
confidence: 99%
“…These methods include flow-mediated dilatation (FMD) and measures of arterial stiffness (such as pulsed wave velocity), which can measure the earliest vascular injury associated with endothelial dysfunction; intima-media thickness (IMT), which can measure the first anatomic changes associated with arterial injury; and biomarkers of vascular health, such as high-sensitivity Creactive protein (hs-CRP), cell adhesion molecules (CAM), and the methylarginines (ie, asymmetric dimethylarginine) [31][32][33]. FMD and IMT have been the most widely used tools in the pediatric population to evaluate preclinical arterial injury attributable to hypercholesterolemia and the effect of other risk factors and changes following therapeutic interventions in the pediatric population [32]. Of these tools, IMT may be the optimal method to estimate the atherosclerotic burden and track longitudinal changes due to risk factor modulation [33].…”
Section: New Approaches For Identifying Youth At Risk For Premature Chdmentioning
confidence: 99%
“…However, therapy is largely guided by laboratory end points, including normalization of serum LDL-C, HDL-C, and triglyceride levels to gauge the success of treatment rather than longterm CHD outcomes. As noted above, the relatively recent application of surrogate vascular markers provides objective information regarding objective vascular changes with treatment [32], although such approaches are still primarily the focus of clinical trials and not day-to-day practice. Multiple issues also complicate treatment of pediatric lipid disorders.…”
Section: Treatmentmentioning
confidence: 99%